Probiotic Bacteria with High Alpha-Gal Content Protect Zebrafish against Mycobacteriosis - Iván Pacheco; Sandra Díaz-Sánchez; Marinela Contreras; Margarita Villar; Alejandro Cabezas-Cruz; Christian Gortázar; José de la Fuente (Pharmaceuticals, 2021)
Mycobacteriosis affects wild fish and aquaculture worldwide, and alternatives to antibiotics are needed for an effective and environmentally sound control of infectious diseases. Probiotics have shown beneficial effects on fish growth, nutrient metabolism, immune responses, disease prevention and control, and gut microbiota with higher water quality. However, the identification and characterization of the molecules and mechanisms associated with probiotics is a challenge that requires investigation. To address this challenge, herein we used the zebrafish model for the study of the efficacy and mechanisms of probiotic interventions against tuberculosis. First, bacteria from fish gut microbiota were identified with high content of the surface glycotope Galα1-3Galβ1-(3)4GlcNAc-R (α-Gal) that has been shown to induce protective immune responses. The results showed that probiotics of selected bacteria with high α-Gal content, namely Aeromonas veronii and Pseudomonas entomophila, were biosafe and effective for the control of Mycobacterium marinum. Protective mechanisms regulating immunity and metabolism activated in response to α-Gal and probiotics with high α-Gal content included modification of gut microbiota composition, B-cell maturation, anti-α-Gal antibodies-mediated control of mycobacteria, induced innate immune responses, beneficial effects on nutrient metabolism and reduced oxidative stress. These results support the potential of probiotics with high α-Gal content for the control of fish mycobacteriosis and suggested the possibility of exploring the development of combined probiotic treatments alone and in combination with α-Gal for the control of infectious diseases.